Optimasi Pemahaman Kader Posyandu terhadap Konsep 'Ibu Bahagia, Keluarga Bahagia' di Kota Malang - Hidayati, Laely; Royani Meisani, Diah; Agnuristyaningrum, Alfi; Salwa Nurwachidah, Nanda; Arumiyati Anwar, Seila (Journal of Issues in Midwifery, 2024)
Posyandu plays a central role in organizing primary healthcare services in Indonesia. Posyandu cadres, as the primary agents providing education to mothers, aim to create healthy and happy families. Family happiness is not only related to physical health but also involves psychological and social dimensions. This activity was conducted to enhance the capacity and understanding of the concept of